2012
DOI: 10.1089/jmf.2012.0050
|View full text |Cite
|
Sign up to set email alerts
|

Convolvulus galaticus, Crocus antalyensis, and Lilium candidum Extracts Show Their Antitumor Activity Through Induction of p53-Mediated Apoptosis on Human Breast Cancer Cell Line MCF-7 Cells

Abstract: Conventional and newly emerging treatment procedures such as chemotherapy, catalytic therapy, photodynamic therapy, and radiotherapy have not succeeded in reversing the outcome of cancer diseases to any drastic extent, which has led researchers to investigate alternative treatment options. The extensive repertoire of traditional medicinal knowledge systems from various parts of the world are being re-investigated for their healing properties. It has been reported that several members of the Convolvulaceae, Iri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 22 publications
0
18
1
Order By: Relevance
“…Altogether, these results support the traditional use of B. perennis in the treatment of cancer. Although Tokgun et al [22] reported the strongest anti-proliferative activity in methanolic extract of C. galaticus against MCF-7 cell line at low concentration (0.32 mu g/mL), we found that the methanolic extract did not have a notable anti-proliferative activity against MCF-7 cell line. But DCM extract of C. galaticus had a moderate anti-proliferative activity against MCF-7 cell line in our study.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Altogether, these results support the traditional use of B. perennis in the treatment of cancer. Although Tokgun et al [22] reported the strongest anti-proliferative activity in methanolic extract of C. galaticus against MCF-7 cell line at low concentration (0.32 mu g/mL), we found that the methanolic extract did not have a notable anti-proliferative activity against MCF-7 cell line. But DCM extract of C. galaticus had a moderate anti-proliferative activity against MCF-7 cell line in our study.…”
Section: Discussioncontrasting
confidence: 93%
“…Furthermore, its flowers are used in the relief of toothache [18,19]. Antibacterial [20,21], antitumor [21] and anticancer activities [22] of C. galaticus have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Increased level of p53 proteins under CBR EtOAc treatment demonstrated that p53 had a major role in apoptotic B16F10 melanoma cell death (Figure 2(c)). Similarly, Tokgun et al reported that medicinal plants of Convolvulus galaticus, Crocus antalyensis , and Lilium candidum extracts showed cytotoxic effect on human breast cancer cells by p53-mediated apoptosis [25]. It seems that CBR EtOAc fraction exerts its antitumor activity through inducing the cellular apoptotic response.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly 5.8/100,000 new breast cancer cases are diagnosed in developed countries and >10.5 new breast cancer cases per 100,000 individuals occur worldwide each year (1). In the early stages of the disease, breast cancer, as in case of a number of other cancers, tends to spread asymptomatically throughout the body and at the point of diagnosis there is an increased likelihood of identification of metastatic lesions (2). Conventional therapies, including surgery, radiotherapy and chemotherapy, have served roles in treatment of breast cancer, but there remain numerous problems in tumor therapy.…”
Section: Introductionmentioning
confidence: 99%